Analysis of Speaking Skill Learning Difficulties in Students of the Arabic Language Education Study Program at State Islamic Institute - Sugirma, Sugirma; Hamid, M. Abdul; K., Agustang (Institut Agama Islam Negeri Curup, 2024)
Speaking skill (maharah kalam) is one of the four main skills that must be mastered by students of the Arabic Language Education Study Program at Islamic universities. The main goal of learning speaking skill is to develop the ability to speak in Arabic fluently, effectively, and accurately. Students are expected to be able to express thoughts, feelings, and information clearly and relevant in a variety of communication contexts. But in reality, there are still students who encounter obstacles in the learning process of speaking skill so that the expected goals are not achieved, as happened to PBA IAIN Ternate students. For this reason, this article discusses the difficulties of students in learning speaking skill at PBA IAIN Ternate with those explored from the results of field research with a qualitative descriptive approach, where the data obtained through questionnaires and interviews are processed by library triangulation. The results show that students of the PBA IAIN Ternate study program are still experiencing difficulties in learning speaking skill, from linguistic and non-linguistic aspects. In the linguistic aspect, it can be seen in the difficulty of understanding vocabulary, stringing sentences, and difficulty in capturing information from the interlocutor. Meanwhile, on the non-linguistic side, it can be seen in the students' lack of confidence in communicating. This affects the achievement of the learning goal of speaking skill, which emphasizes communication skills using Arabic.